Effect of annealing on performance of ZnO thin film transistors. (2nd January 2019) - Yi, Geum Ran; Kim, Han Sol; Lee, Do Hyung; Kim, Bada; Kim, Chang Kyo
Abstract: ZnO thin film transistors (TFTs) were fabricated through annealing of ZnO thin films at temperatures ranging from 250 °C to 400 °C. ZnO nanoparticles (NPs) synthesized via a sol-gel method were used as an active layer for ZnO TFTs due to their high Hall mobility, and ZnO thin films were produced by spin-coating a precursor solution of ZnO NPs, followed by annealing at 250 °C to 400 °C. When the grain size increases with increasing annealing temperature, the Hall mobility of the ZnO thin films increases due to decrease of the grain boundary density. As the annealing temperature increased from 250 °C to 350 °C, field effect mobility (µFE ) and on-to-off (Ion /Ioff ) ratio increased while threshold voltage (Vth ) and subthreshold swing (S-S) decreased. This is likely due to an increase in the conductivity of the ZnO thin film according to the increasing grain size. 350 °C-annealed ZnO TFT exhibited the best electrical properties with a Vth of 4.8 V, an Ion /Ioff ratio of 10 4, and a field-effect mobility (μFE ) of 0.2 cm 2 V −1 s −1 .